Min al-Ḥarbi ḷla al-ḷṣlaḥ wa al-Salam: Tafsiru Āyāti āl-Ǧihād ʿala Ḍawʾi Maqaṣidihā - Hasbillah, Ahmad Ubaydi (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2022)
The interpretation of jihadi verses has been still within the framework of the vision of "preserving one of the six primary needs" and has not yet come to the vision of the preservation of the six needs. In fact, jihad is the peak of militancy in Islam that must pay attention to all needs and needs in Islam. This research aims to conduct an in-depth study of the purpose of jihad depicted in the verses of the Qur'an and how it is applied and achieved in the present era.  This study used the maqasidi maudu'i method to determine the verses of jihad as well as the maqasidi aspects in the verse. Aspects of maqasidi are traced using the language analysis commonly used in ushul fiqh. The maqasid findings were then developed with a new concept of the six primary human needs (al-daruriyat al-sitt) and implemented in today's needs in accordance with the concept (ihya' al-Qur'an). Referring to the ideal concept of maqasid jihad in the Qur'an, the practice of jihad can be stated that it is still not comprehensive because it is only one way to achieve the six primary needs of man while ignoring the rest and even eliminating it to the point of damaging it. At the same time, the study also highlights the importance of developing the vision-mission (maqasid) that jihadi verses aim for: from the generally "to defend and attack" to the mission of "reform and peace." The research also recommends reviving this vision of reform and peace in reviving the maqasid of jihadi verses in various countries.